2022
DOI: 10.21203/rs.3.rs-1695204/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Postoperative analgesic effect of dexmedetomidine combined with TPVB applied to open gastrectomy for gastric cancer

Abstract: Purpose: This study is aimed to investigate the analgesic effect of combined dexmedetomidine and thoracic paravertebral nerve block (TPVB) on gastric cancer (GC) patients undergoing open gastrectomy. Methods: From May 2019 to Nov 2020, a total of 80 GC patients preparing for open gastrectomy were enrolled in our hospital and were divided into the ropivacaine (RO) group and the ropivacaine + dexmedetomidine (RD) group ad libitum. All of the patients underwent TPVB. The characteristics, usage of patient-controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…This study selection process is summarized in the PRISMA flow chart ( Figure 1 ). According to Cochrane’s Risk of Bias 2 (RoB2) assessment, seventeen RCTs [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] were considered to be low-risk and three RCTs [ 30 , 31 , 32 ] had some concerns. Moreover, the quality of the included studies is summarized in Supplementary Materials (Table S2) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This study selection process is summarized in the PRISMA flow chart ( Figure 1 ). According to Cochrane’s Risk of Bias 2 (RoB2) assessment, seventeen RCTs [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] were considered to be low-risk and three RCTs [ 30 , 31 , 32 ] had some concerns. Moreover, the quality of the included studies is summarized in Supplementary Materials (Table S2) .…”
Section: Resultsmentioning
confidence: 99%
“…Two out of three abdominal cancer surgery reported on 48 h postoperative sufentanil consumption [ 26 , 27 ]. The meta-analysis of those studies concluded that sufentanil consumption was significantly lower in the dexmedetomidine group (SMD = −1.34 [95% CI −2.29 to −0.40], p = 0.005, I2 = 84%, random effects) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations